IMPLEMENTASI KEPUTUSAN BUPATI KAMPAR NOMOR 660-328/IV/2019 TENTANG PENGAKUAN HUTAN ADAT GHIMBO BONCA LIDA - Rizal, Hanna Ramadani; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
ABSTRAK Implementation of Kampar Regent Decree Number: 660-328/IV/2019 concerning the recognition of the Ghimbo Bonca Lida Customary Forest regarding the determination and management of customary forests is very important and needs to be considered by the local government. Decisions from the local government must be implemented as well as possible so that management or existing resources can be preserved wisely with existing regulations. The regent's decision is important in the management of customary forests from forest exploitation activities. Problems arise because the contents of the decision do not match what happens in the field. This study aims to describe a clear picture of the Kampar Regent's Decree Number: 660-328/IV/2019. In achieving these research objectives, the researcher uses George C. Edward III's policy implementation theory. The research method used is a qualitative method by explaining descriptive data. The type of research data used is primary in the form of data obtained from research informants and secondary in the form of data obtained from related documents. Then the research location is in Kampa, Kampa Village, Kampa District, Kampar Regency. The results of the study found that the implementation of the Kampar Regent's Decree Number: 660-328/IV/2019 concerning the recognition of the Ghimbo Bonca Lida Customary Forest has not been running optimally due to deficiencies in communication indicators where there is no interaction from either the government or village institutions in carrying out the operational management of the customary forest, and resources that are not yet competent in implementing the decree, related to the attitude/disposition of the absence of a proactive attitude from the village institution authorized to manage the customary forest, the bureaucratic structure is quite good with the grouping of responsibilities and sections in managing the customary forest but implementation to the community has not been educated and guided in the structure so that the role of the community is still not optimal in managing the customary forest. Keywords: implementation, decision, communication, resources, attitude/disposition, bureaucratic structure